CHANGE DETECTION IN MOSUL DAM LAKE, NORTH OF IRAQ USING REMOTE SENSING AND GIS TECHNIQUES - Al-Obaidi, M.A.; AL-Timimi, Y.K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to demonstrate the spatial changes of Mosul Lake using change detection Techniques. Water bodies, an integral part of the Earth’s hydrological cycle, such as rivers, ponds, lakes, wetlands, and reservoirs, have a major effect on climate change and global warming. one of the most imperative vital activities in Iraq for the administration of its water resources is Mosul Dam Lake. The lake has changed in the water surface due to the severe anthropogenic activities, climate change, the monthly inflows received from the Tigris River, and the controlling of water imports by neighboring countries, and the territorial policy. Remote sensing techniques and Geographic Information System ArcGIS 10.3 software were used in the present study for processing the images and managing the database of each image were downloaded from the united states geological survey(USGS). Spectral Water indices, includes Normalized Difference Water Index (NDWI) and unsupervised classification were used to extracting water bodies and computing water area, the images difference technology was used to detect a different image and capture changes area for 20 years, the method has been applied to subsets of the Landsat series images that acquired during April in 2000, 2005, 2010,2015 and 2020. The results showed that there is an increase in the area of Mosul dam lake from its original area in 1986 which was 244 km2 in a rate of (15.1,31.14,13.11, and 20.9) % for periods (200,2005,2015, and 2020) respectively, and a decrease in water area with a rate of 7.78% for period 2010, that means the water surface area fluctuated over the period given, increasing and decreasing in the water surface. the minimum water surface area was recorded in 2010 of about 225 km2, whereas, the maximum area of the lake was found to be 320 km2 in 2005. the total average increasing and decreasing change detection were 25.4550174 and 19.7851824 km2 respectively.